Critical analysis of the effects of e-commerce on taxation - Hirschowitz, Debrah Ann (My University, 2019)
E-commerce has become a significant part of the global economy and will continue to grow. However, e-commerce doesn’t only provide exceptional growth opportunities, but also creates considerable challenges in terms of taxation. Due to the nature of e-commerce, various commercial activities are carried out in cyberspace where trade is not confined by geographical boundaries. This study is motivated by the key importance of understanding the taxation landscape in a rapidly growing digital economy. In this study the impact of e-commerce on taxation is explored by means of a systematic literature review. The primary research question was: what is the impact of e-commerce on taxation? In order to address the research question, secondary questions were formulated to firstly attend to the broader tax challenges in a digital economy and to determine how these challenges lead to tax avoidance practices. Secondly, the impact of e-commerce on taxation was explored specifically in terms of the artificial avoidance of the permanent residence status. Thirdly, the prevention of artificial avoidance of the permanent residence status was reviewed as well as investigating what practices have been put in place by some countries to protect their tax bases. Based on the research question, the objective of this study was to explore and provide an overview of the existing literature to determine what the impact of ecommerce has been in terms of the challenges it poses to taxation. Due to the exploratory nature of the research, it was a qualitative study within the interpretivist paradigm. In this study, the aim was not to identify a specific theory, but rather to explore the existing literature and provide an overview of how e-commerce affects taxation within the framework of the primary and secondary research questions by means of systematic literature review. In terms of the findings, the broader tax challenges were identified as: nexus, data and value-creation, the characterisation of payments and the impact of highly digitised business models. It was further established that these challenges created an environment where significant tax avoidance practices are employed by highly digitised organisations. The key tax avoidance practices were identified as: avoiding withholding tax, the use of preferential tax regimes, artificial internal trading of intangibles, internal debt shifting, transfer pricing and avoiding taxable presence. This study has certain limitations, since the full domain of e-commerce and taxation is vast and complex and beyond the scope of a research report. Therefore, the key challenge that was explored is the artificial avoidance of the permanent residence status which is an issue that lies at the heart of the nexus issue since a PE normally requires some sort of physical presence which is not necessarily the case in the digital economy. This study contributes to the existing body of knowledge as a useful assessment of the impact of e-commerce on the digital economy as well as the associated tax avoidance practices. Furthermore, in conducting the research, it became apparent to the researcher that South Africa has very limited exposure in the field of the tax challenges relating to e-commerce. This research could therefore provide some insight into some of the key tax challenges identified in the international arena and this study could provide a starting point from a South African perspective.
A research report submitted to the Faculty of Commerce, Law and Management at the University of Witwatersrand in partial fulfilment of the requirements for the degree of Master of Commerce
Keywords: Electronic commerce--South Africa; Income tax--South Africa; Electronic commerce